The effect of treatment of obstructive sleep apnea syndrome on overactive bladder symptoms - Deger,Mutlu (2021)
SUMMARY OBJECTIVE: To evaluate the effect of the treatment of obstructive sleep apnea syndrome on overactive bladder symptoms. METHODS: All patients who applied to the outpatient clinic with complaints of snoring and apnea were evaluated by polysomnography between years 2017 and 2019. obstructive sleep apnea syndrome severity was evaluated according to the apnea-hypopnea-index. All patients were filled with questionnaire form as overactive bladder symptoms score, international quality of life, international consultation on incontinence questionnaire short-form, and 3-day bladder diary before polysomnography and three months after continuous positive airway pressure therapy and surgical treatment. RESULTS: A total of 125 patients, 34 (27.2%) patients with mild obstructive sleep apnea syndrome, 27 (21.6%) patients with moderate obstructive sleep apnea syndrome, and 64 (51.2) patients with severe obstructive sleep apnea syndrome were included in the study. The prevalence of overactive bladder symptoms in three obstructive sleep apnea syndrome groups were 67.6, 53.8, and 48.4%, respectively, and there was no statistical difference between the groups (p=0.190). obstructive sleep apnea syndrome treatment such as surgical treatment or continuous positive airway pressure therapy was applied to 45.5% (31 patients) patients with obstructive sleep apnea syndrome and overactive bladder. Three months after treatment, the overactive bladder symptoms score significantly decreased from 16.1±7.9–12.80±9.82, international quality of life was significantly increased from 105.0±23.2–110.4±22.2, and incontinence questionnaire short-form decreased from 11.9±4.0–10.4±5.6 (p=0.009, p=0.023, and p=0.248, respectively). There was a significant decrease between before and after treatment in terms of mean day-time frequency and mean urgency episodes of patients (p=0.007, p=0.002). CONCLUSIONS: Both surgery and continuous positive airway pressure treatment of obstructive sleep apnea syndrome improved overactive bladder symptoms, overactive bladder symptoms score, international quality of life, day-time frequency, and urgency episodes.